Gut microbes, ageing & organ function: a chameleon in modern biology?. Issue 9 (14th August 2019) - Reza, Musarrat Maisha; Finlay, B Brett; Pettersson, Sven
Abstract: All species, including humans, are cohabited by a myriad of microbial species, which massively influences body function in a diet‐, exercise‐ and age‐dependent manner. The microbiome composition differs between individuals, partly due to the polymorphic immune system, as well as the environment, making the microbe–host interplay unique in each one of us. Ageing is a gradual loss of function in part due to reduced repair mechanisms and accumulation of tissue damage through mechanisms largely unknown. Accumulating evidence suggests that our indigenous microbes, a known major regulator of human physiology, are also connected to regulate the ageing process through signalling pathways and metabolites though the biological mechanisms are unknown. At an ageing meeting in Singapore in 2018, investigators discussed the current understanding of microbe regulation and its impact on healthy ageing. This review summarizes the highlights from the meeting and conveys some of the new ideas that emerged around gut microbes and the biology of ageing. While highly speculative, an idea emerged in which gut microbes constantly respond and evolve to environmental cues, as part of an ageing process, thus serving as a second messenger to support and attenuate organ decline in a diet‐, gender‐ and age‐dependent manner. Abstract : From the role diet plays in shaping the gut microbiome composition and function to how it can modulate host responses to diet, the review by Reza, Finlay and Pettersson discuss the interesting subject of healthy aging and the gut microbiome.